2011
DOI: 10.1002/asl.357
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ESI tendency and Indian monsoon rainfall: a possible mechanism

Abstract: In this article, we have studied spatial and temporal variabilities of temperature and zonal wind field over 90 • -0 • N, 90 • W-90 • E during contrasting phases of Effective Strength Index (ESI) tendency and its relationship with Indian summer monsoon rainfall (ISMR). During positive (negative) ESI tendency, there is winter-time anomalous cooling (warming) over western Eurasia surrounding Moscow but magnitude of warming is stronger than cooling. The correlation analysis also suggests that negative ESI tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…ESI-tendency from winter to spring is defined as the difference, i.e., April minus January ESI values. Kakade and Kulkarni (2012) pointed out that the relationship between ISMR and ESI-tendency is statistically significant in negative phase and is insignificant in positive phase of ESI-tendency. Further, they have also shown that the evolution of surface temperature from winter to spring is exactly opposite during contrasting phases of ESI-tendency.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…ESI-tendency from winter to spring is defined as the difference, i.e., April minus January ESI values. Kakade and Kulkarni (2012) pointed out that the relationship between ISMR and ESI-tendency is statistically significant in negative phase and is insignificant in positive phase of ESI-tendency. Further, they have also shown that the evolution of surface temperature from winter to spring is exactly opposite during contrasting phases of ESI-tendency.…”
Section: Datamentioning
confidence: 99%
“…Thus the behaviour of ESI from January to April is the critical factor between excess and deficit monsoon activity over India. Kakade and Kulkarni (2012) have shown that there is a clear line of demarcation in the relationship of ESI-tendency and Indian summer monsoon rainfall (ISMR) during contrasting phases of ESItendency. The relationship between ISMR and ESI-tendency is statistically significant in negative phase and is insignificant in positive phase of ESI-tendency.…”
Section: Lrf Of Summer Monsoon Rainfall Over Rc Regionsmentioning
confidence: 99%
“…Therefore their influence on European temperature is different in two phases of ESI-tendency [10]. With this background, we have considered monthly evolution of AO pattern during contrasting phases of ESI-tendency which is important to understand the relationship of geophysical parameters over the Arctic with ISMR.…”
Section: Arctic Circulation and Ismr During Contrasting Phases Of Esimentioning
confidence: 99%
“…Thus ESI-tendency from January to April is a precursor for monsoon circulation over Indian subcontinent. Kakade and Kulkarni [10,11] have discussed the evolution of NAO and SO from winter to spring and their impact on European temperature changes during contrasting phases of ESI-tendency. The present study mainly deals with the relationships among AO, Arctic weather and ISMR on interannual scale during positive and negative ESI-tendency.…”
Section: Introductionmentioning
confidence: 99%
“…Kakade and Kulkarni (, ) have demonstrated that evolution of ST and SLP from winter to spring changes with the phase of effective strength index (ESI) tendency. Kakade and Kulkarni () obtained two separate multiple regression equations for LRF of the ISMR during contrasting phases of the ESI tendency using independent cluster parameters of ST and SLP.…”
Section: Introductionmentioning
confidence: 99%